Water Management in Hadith Perspective - Ihya, M Saifuddin (Journal of Hadith Studies, 2018)
This article discusses the concept of water management in the perspective of Hadith. Using the library study method, this article found that water is one of the most important resources for life considering that the existence of water in the life of living things is an inevitability because there is no life without water because all living things, both humans, animals, and plants, need water. It is important for people to always preserve and maintain the water used, in order to maintain their sustainability by conducting good water management. Water is something that is needed by all living things, including humans. Islam as a religion of raá¸¥mat li al- â€˜ÄlamÄ«nestablishes the existence of joint ownership of things that are much needed (á¸arÅ«rÄ«)) for all human beings. therefore, Islam brings out everything whose existence and benefits do not depend on special efforts from the scope of individual ownership, so that its ownership is shared, one of which is water.